Decreasing Popularity Of Ceramic Tourism Village Of Dinoyo Malang In New Media Age - Fathul Qorib; Amanah Rakhim Syahida (Jurnal Ilmu Komunikasi, 2018)
Cyber media and social media applications become the key of many tourist attractions in Indonesia. In Malang city, East Java, the local government strengthens the tourism sector by building its tourism village. Utilizing the new media network, Malang is now known as the pioneer of Tourism Village. Unfortunately, as the number of tourism villages becomes famous, there is one famous tourism village that was previously famous, even falling in popularity, namely ‘Kampung Wisata Keramik Dinoyo’. This study aimed to determine the causes of decreasing popularity of the village using public relations theory and descriptive qualitative research methods. In-depth interview were administered to the Chairman of Paguyuban Kampung Wisata Keramik Dinoyo, government, and shop owners in Dinoyo Village. The results showed that Kampung Keramik Dinoyo removed many sectors in the field of public relations, especially the use of new media. It was suggested to tourism village to fully use the new media access in order to improve its image so its popularity also increased.